2018
DOI: 10.1002/mabi.201800389
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐Based Imaging of Clinical Transplant Populations Encapsulated in Protective Polymer Matrices

Abstract: A recent clinical trial proves that autologous olfactory mucosal cell (OMC) transplantation improves locomotion in dogs with naturally occurring spinal injuries comparable to human lesions. However, not all dogs respond to the treatment, likely due to the transplantation procedures involving injections of cell suspensions that are associated with cell death, uneven cell distribution, and cell washout. Encapsulating cells in protective hydrogel matrices offers a tissue engineering solution to safely achieve 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“… 33 Clinical transplantation would likely occur within this 3-day time-period, if not immediately after encapsulation (prior to gelation) if a percutaneous injectable approach were used. Previous work has also shown high OEC viability after hydrogel encapsulation in lower concentration collagen hydrogels, 39 Matrigel 67 and polylactic- co -glycolic acid (PLGA) 68 hydrogels, although not in alginate. 67 Collagen hydrogels were used in this study because of their prior use in experimental SCI repair, 12 , 69 including for cell encapsulation, 70 , 71 and because collagen is highly biocompatible; 1 a variety of collagen products from various sources have been FDA approved for use in the nervous system, 72 including as medical sealants for dural repair.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 33 Clinical transplantation would likely occur within this 3-day time-period, if not immediately after encapsulation (prior to gelation) if a percutaneous injectable approach were used. Previous work has also shown high OEC viability after hydrogel encapsulation in lower concentration collagen hydrogels, 39 Matrigel 67 and polylactic- co -glycolic acid (PLGA) 68 hydrogels, although not in alginate. 67 Collagen hydrogels were used in this study because of their prior use in experimental SCI repair, 12 , 69 including for cell encapsulation, 70 , 71 and because collagen is highly biocompatible; 1 a variety of collagen products from various sources have been FDA approved for use in the nervous system, 72 including as medical sealants for dural repair.…”
Section: Discussionmentioning
confidence: 96%
“…They have been shown to improve walking (BBB score) in two recent meta-analyses of rodent experiments, 36,37 have shown efficacy in a clinical trial using the canine model 33 and have undergone phase 1 human trials demonstrating safety. 38 OECs have high viability encapsulated in collagen, 39 supporting the use of collagen as a protective delivery vehicle for OEC transplant.…”
Section: Introductionmentioning
confidence: 95%
“…Further, as surgical grade materials in highly aligned conformations are developed for peripheral nerve injuries, we can predict similar advances will ensue with CNS materials that show mimicry of native spinal cord micro-architecture. We recently also showed that pre-labelling of transplant populations with clinical grade nanoparticles can be used to detect transplant cells incorporated into polymer matrices using magnetic resonance imaging [56], offering further advantages for clinical cell therapy. Further testing of such encapsulating matrices using live animal models of neurological injury with assessment of functional neurological recovery, and assessment of the compatibility of the biomaterials to support growth of human transplant populations is needed to advance the use of such an approach for clinical cell therapy applications.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Syková et al demonstrated rapid integration of IONP-loaded MSC-seeded hydrogels, based on derivatives of 2-hydroxyethyl methacrylate (HEMA) and 2-hydroxypropyl methacrylamide (HPMA), into hemisected rat spinal cords, demonstrating their potential suitability for bridging voids after spinal cord injury [ 457 ]. Finally, Adams et al presented a potential method in which IONP-labeled canine olfactory mucosal cells (OMCs) were encapsulated in collagen hydrogels to increase the low viability of graft cells for implantation at injured sites, particularly the spinal cord, to improve regeneration outcomes [ 502 ].…”
Section: Pns and Cns Regenerationmentioning
confidence: 99%